Reflections on land policy and the independence settlement in Kenya. (22nd August 2016) - Van Arkadie, Brian
ABSTRACT: This essay reflects on a personal participation in policy-making in relation to Kenya, almost 50 years ago. The policies that the British colonial authorities pursued in respect of the transfer of land to black Kenyans were crucial in the design of the decolonisation framework which managed the transition from colonial to self-rule. The outcome of the land policy was the creation of a black middle class of prosperous farmers, the preservation of the position of white farming, a transition to capitalism and the creation of a black capitalist class eagerly embraced by Kenyatta and his successors, but not solving the problems of land hunger and accompanying rural poverty which continue today.